1968
DOI: 10.1128/jb.95.6.2358-2364.1968
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Ultrastructure of Streptomyces venezuelae

Abstract: Streptomyces venezuelae is a filamentous bacterium with branching vegetative hyphae embedded in the substrate and aerial hyphae bearing spores. The exterior of the spore is inlaid with myriads of tiny rods which can be removed with xylene. The spore wall is approximately 30 nanometers thick. Occasionally, it can be seen that the plasma membrane and the membranous bodies within a spore are connected. The spore's germ plasm is not separated from the cytoplasm by a nuclear envelope. The cell walls of the vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

1970
1970
1982
1982

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 18 publications
(11 reference statements)
3
22
0
Order By: Relevance
“…Almost all of the studies on the chemical composition of the cell walls of these organisms are restricted to qualitative amino acid analyses (34,46,68,69,76,218,219,225,257,372,375,428). The primary structure of the peptidoglycans has been determined in only a very few cases.…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…Almost all of the studies on the chemical composition of the cell walls of these organisms are restricted to qualitative amino acid analyses (34,46,68,69,76,218,219,225,257,372,375,428). The primary structure of the peptidoglycans has been determined in only a very few cases.…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…Amino acid analysis showed that C-cell walls contained more alanine than G-cell walls but both contained approximately equimolar amounts of DAP and lysine. According to Cummins and Harris [2] and Bradley and Ritzi [1], chemical compositions of Streptomyces species cell walls were reported to be amino acids and amino sugars such as alanine, glutamic acid, glycine, muramic acid, DAP and glucosamine. DeWeese et al [3] reported that Actinomyces propionicus differed significantly from other Actinomyces species in that it contained DAP and lysine as major cell wall components.…”
Section: Discussionmentioning
confidence: 99%
“…Streptomycetes are prokaryotic organisms which are characterized by the lack of membrane structures surrounding their nucleoids [ 1,[4][5][6]13,16,17]. Studying the intracellular development of several newly isolated Streptomyces phage by electron microscopy, we observed trilamellar membranes surrounding the nucleoids of the host organism after infection by phage SH12.…”
Section: Introductionmentioning
confidence: 99%